Investigation of microalgae culture by autoflocculation methodologies - Van Anh, Le Thi; Ngoc Thu, Tran Thi; Thi Dong Phuong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Harvesting of microalgae from their different cultivation media has pointed out challenges in resolving the problems of flocculation. These challenges must be faced with a  suitable method for inducing flocculation that avoid or limit the microalgae’s contamination. This study developed the fundamental experiments with a support of chemicals and some bacteria strains inducing the flocculation of Chlorella vulgaris SAG 211-19.  Particularly, the determination of minimum content of Mg2+, Ca2+, E. coli ATCC 85922 and Bacillus subtilis MT300405 was effectuated with co-cultivation of microalgae and set up in batch culture in Bold’s Basal Medium. As a result, the adjustment in 25 minutes of 199.2 mg/L CaCl2.2H2O, 50 mg/L KH2PO4, and of 141 mg/L MgSO4.7H2O induced a microalgal settling efficiency of 81% and 70%, respectively. Meanwhile, the perfomance of microalgal removing reached up to 83.6% and 84% by the inoculation into microalgal culture media of a minimum initial cell density of 8.1 ´ 105 CFU/mL of Bacillus subtilis MT300405 and 12 ´ 105 CFU/mL of E. coli ATCC 85922, respectively. The flocculation of microalgal cells by bacterial inoculation did not require a high pH adjustment as in the case of salt addition.